PROFESSIONAL COMPETENCE OF THE TEACHER AND IMPROVEMENT OF PEDAGOGICAL SKILLS - Jumaniyozova Muhayyo Tojiyevna (Web of Journals Publishing, 2025)
This article will talk about the peculiarities of adult education and the issues of applying a creative approach to adult education.
Keywords: Educational needs, adult education, creativity, competence.